PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN (Studi Pada PT. Moka Teknologi Indonesia Khusus Kantor Pusat Jakarta Barat) - Dewi, Marchelina Sukma (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
PT. Moka Teknologi Indonesia is an associate company of Gojek whic provides various solutions for offline & online sales needs. This research is determine compensation, leadership style and position promotion on employ job satisfaction at PT. Moka Technology Indonesia. The object of this researc is employees at PT. Moka Teknologi Indonesia This research was conducted o 114 customers. The sample used was the Non-Probability Sampling Techniqu which was selected by Saturated Sampling where all populations were take namely 114. This type of research is causal analysis with a quantitati approach. The sample in this study were 114 customers. The data collectio technique used a questionnaire. The data collection method uses a survey, wi the research instrument being a questionnaire. The data analysis method us the Partial Least Square (PLS) analysis tool. This study proves th compensation has a significant positive effect on job satisfaction, leadersh style has a significant positive effect on job satisfaction, promotion has significant positive effect on job satisfaction. This study also explains that jo satisfaction is influenced by the model by 98.3% while the remaining 1.7% influenced by other variables not examined in this study.